A new eucryptodiran turtle from the Early Cretaceous Jiufotang Formation of western Liaoning, China - Zhou, Chang-Fu (Zootaxa, 2010)
A new eucryptodiran turtle from the Jiufotang Formation of Lamadong, Jianchang County, represents the third turtle taxon, Liaochelys jianchangensis gen. et sp. nov., from the Jehol Biota of western Liaoning Province, China. This taxon is diagnosed by a character combination including a midline contact of the prefrontals, vertebrals wider than long, third costals strongly expanded distally, and a medial contact of the eighth costals. A preliminary cladistic analysis places Liaochelys jianchangensis along the phylogenetic stem of Cryptodira in a position more derived than the taxa, Manchurochelys manchoukuoensis and Ordosemys liaoxiensis, known from the underlying Yixian Formation. This discovery opens a new window into the osteology and evolution of primitive eucryptodiran turtles.